Pengaruh Profitabilitas dan Ukuran Perusahaan Terhadap Pengungkapan Tanggung Jawab Sosial Perusahaan di Bursa Efek Indonesia - Putri, Ni Made Deviarini; Animah, Animah; Astuti, Widia (E-Jurnal Akuntansi; Vol 32 No 4 (2022)DO - 10.24843/EJA.2022.v32.i04.p11, 2022)
Disclosure of social responsibility is a form of delivery from the company to stakeholders for the commitment made by the company to maintain and maintain the components affected by the operational activity process based on the Triple Bottom Line concept. The research has the aim of knowing the effect of profitability and company size on the disclosure of social responsibility. The proxy used in this study is the level of profitability which is proxied through the ROA ratio and company size which is calculated using the natural logarithm of total assets. The method for determining the sample uses purposive sampling, with a total sample of 62 manufacturing companies. Analysis using multiple linear regression. The results showed that profitability and firm size had a positive effect on the disclosure of social responsibility. Keywords: Corporate Social Responsibility Disclosure; Profitability; ROA; Firm Size.